Soliton solutions and conservation laws for lossy nonlinear transmission line equation - Tchier, Fairouz; Yusuf, Abdullahi; Aliyu, Aliyu Isa; İnç, Mustafa (Academic Press Ltd- Elsevier Science Ltd, 2017)
In this article, the Lie symmetry and Ricatti-Bernoulli (RB) sub-ODE method are applied to obtain soliton solutions for nonlinear transmission line equation (NLTLs). The NLTLs is defined to be a structure whereby a short-duration pulses known as electrical solitons can be invented and disseminated. We compute conservation laws (Cls) via a non-linear selfadjointness approach. A suitable substitution for NLTLs is found and the obtained substitution makes the NLTLs equation a non-linearly self-adjoint. We establish Cls for NLTLs equation by the new Cls theorem presented by Ibragimov. We obtain trigonometric, algebraic and soliton solutions. The obtained solutions can be useful for describing the concentrations of transmission lines problems, for NLTLs. The parameters of the transmission line play a significant role in managing the original form of the soliton. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: NLTLs; Symmetries; RB sub-ODE; Nonlinear self-adjointness and Cls